Theorizing The Social Acceptance of Appropriate Technological - Meredian Alam (STI Policy and Management Journal, 2013)
Appropriate technology is actively involved in the discourse of the developing of environmental friendly technology that can be used by local household in the developing countries. Still, many experts neglect the social dimension that may affect the sustainability in the pre and after construction processes. By acknowledging the theory of appropriate technology and social construction of technology, this paper is in attempt to shed the light of social dimensions that are often embodied in the social setting in which technology is constructed.